Printed recyclable and self-poled polymer piezoelectric generators through single-walled carbon nanotube templating. Issue 3 (20th December 2019) - Shepelin, Nick A.; Sherrell, Peter C.; Goudeli, Eirini; Skountzos, Emmanuel N.; Lussini, Vanessa C.; Dicinoski, Greg W.; Shapter, Joseph G.; Ellis, Amanda V.
Abstract : High-performance, unpoled and recyclable piezoelectric generators are produced by combining dipole templating via single-walled carbon nanotubes with shear-induced polarisation via 3D printing of fluoropolymers. Abstract : With an increasing global energy demand, along with a rising uptake of portable electronic devices, it is of great importance to investigate the viability of alternative energy harvesting technologies. Flexible piezoelectric generators (PEGs) are able to convert mechanical energy to electricity, making them an ideal candidate to decrease reliance on conventional energy sources and to power flexible, portable and implantable electronics. In this study, we show a low-energy production pathway for transparent PEGs based on poly(vinylidene fluoride- co -trifluoroethylene) (PVDF-TrFE) via shear-induced alignment of its dipoles through extrusion printing, complemented by spatial dipolar templating onto single-walled carbon nanotubes (SWCNTs) at low concentrations (<0.05 wt%). The resulting composite PEGs show up to a 500% enhancement in the piezoelectric charge coefficient d 33 relative to extrusion printed pristine PVDF-TrFE, with similar enhancements in energy harvesting, exhibiting a power density of up to 20 μW cm −3 at 0.02 wt% SWCNTs. The extrusion printed composite PEGs show recyclability using only a green solvent (acetone) and are found to exhibit piezoelectric energy harvesting with a power density of up to 71 μW cm −3 upon reprinting, overcoming two of the most significant hurdles towards commercial production of flexible PEGs.